Impacts of Climate Change on Agriculture and Adaptive Strategies in China - Rui-li LI; Shu Geng (Journal of Integrative Agriculture, 2013)
China is the world's most populous country and a major emitter of greenhouse gases. Consequently, China's role in climate change has received a great deal of attention, whereas the impact of climate change on China has been largely ignored. Studies on the impacts of climate change on agriculture and adaptation strategies are increasingly becoming major areas of scientific concern. However, the clear warming that has been sounded in China in recent decades has not been matched with a clear assessment of the impact of climate change on China's water resources and agriculture. In the present study, we review observations on climate change, hydrology, and agriculture in China and relate these observations to likely future changes. We also analyse the adaptive strategies in China's agriculture.